1995
DOI: 10.1097/00005373-199508000-00022
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Emergent Abdominal Sonography after Blunt Trauma

Abstract: In North America, the role of emergent abdominal sonography [ultrasonography (US)] after blunt trauma requires further definition. The purpose of this prospective study was to compare US to the gold standards, diagnostic peritoneal lavage (DPL), and computed tomography (CT), in a population of adults after blunt trauma. In 206 adults who required either CT or DPL to assess possible abdominal injury, US was performed, before DPL or CT, and was aimed at the detection of intraperitoneal fluid. The mean Injury Sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(33 citation statements)
references
References 18 publications
0
31
0
1
Order By: Relevance
“…Ultrasound Ultrasound is a rapid, portable, and reliable method for screening of patients with sustained abdominal trauma for the presence of hemoperitoneum [13,15,16,17,27]. Emergency sonography for trauma is performed bedside and simultaneously with physical assessment, resuscitation, and stabilization within the first minutes of the patient's arrival.…”
Section: Imaging Strategies In Patients With Abdominal and Pelvic Traumamentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound Ultrasound is a rapid, portable, and reliable method for screening of patients with sustained abdominal trauma for the presence of hemoperitoneum [13,15,16,17,27]. Emergency sonography for trauma is performed bedside and simultaneously with physical assessment, resuscitation, and stabilization within the first minutes of the patient's arrival.…”
Section: Imaging Strategies In Patients With Abdominal and Pelvic Traumamentioning
confidence: 99%
“…Several studies have shown that in the hands of an experienced operator, US allows detection of free intraperitoneal fluid with a very high accuracy [12,13,14,15,16,17]. Most trauma surgeons rely on CT as the next diagnostic step for this secondary evaluation of the hemodynamically stable patient with suspected abdominal injury.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of US for the detection of free intraperitoneal fluid is generally considered to be excellent, and there is general consensus that abdominal US is more cost-effective than diagnostic peritoneal lavage (DPL) [7]. Although DPL has a high false-positive rate, US has a good overall specificity to suggest an intra-abdominal injury [8,9,10]; thus, there is general consensus that in a victim of polytrauma who is hemodynamically unstable at admission, the presence of a major quantity of free intraperitoneal fluid on US in a hemodynamically unstable polytrauma warrants emergency laparotomy.…”
Section: Ultrasonographymentioning
confidence: 99%
“…It is after all an impressively rapid technique (< 3 min) providing almost instant information, particularly in the patient with a large hemoperitoneum. The literature describes a specificity, sensitivity and accuracy for free fluid ranging from 98% to 100%, 81% to 92% and 96% to 99%, respectively [41,46,48,62,[64][65][66][67][68][69][70] (Table 5).…”
Section: Ultrasoundmentioning
confidence: 99%
“…There still are limitations to the visualization of all areas of the abdomen, and several studies have documented missed bowel injuries [1,12,75]. An additional disadvantage is the need for general anesthesia, and there is evidence that a CO 2 pneumoperitoneum can increase intracranial pressure, compromise intestinal circulation, and may be detrimental to hypovolemic patients [47,64,76,77]. Further research is nessessary, but for the time being, extreme caution and extensive monitoring are mandatory if CO 2 laparoscopy is used for diagnosis and treatment of trauma victims with possible associated head trauma.…”
Section: Diagnostic Laparoscopymentioning
confidence: 99%